Blood sampling for metanephrines comparing venipuncture vs. indwelling intravenous cannula in healthy subjects - Eijkelenkamp, Karin; van Geel, Eva H.; Kerstens, Michiel N.; van Faassen, Martijn; Kema, Ido P.; Links, Thera P.; van der Horst-Schrivers, Anouk N.A. (Clinical chemistry and laboratory medicine, 2020)
Background To diagnose pheochromocytoma or sympathetic paraganglioma, guidelines recommend blood sampling after at least 30 min of supine rest and using an indwelling intravenous cannula is preferred. Although blood sampling by venipuncture is more convenient and cost-effective, it is unknown whether venipuncture affects plasma concentrations of free metanephrines (MNs). We therefore investigated whether there is a difference in plasma concentrations of free MNs collected by venipuncture or by an intravenous cannula. Methods We included 22 healthy participants (12 men and 10 women, median age 26 years). We collected blood using an indwelling cannula and venipuncture to determine plasma concentrations of free MNs and catecholamines, and calculated the median of the individually calculated absolute and relative differences. Results Plasma concentrations of free MN, normetanephrine (NMN) and epinephrine were higher with blood sampling using venipuncture compared to that when using an indwelling cannula. The median (interquartile range [IQR]) difference was MN 0.020 (-0.004 to 0.040) nmol/L, median percentage difference 20.5% (-2.4 to 35.2%), NMN 0.019 (-0.004 to 0.077) nmol/L, median percentage difference 4.6% (-1.1 to 25.4%) and epinephrine 0.022 (0.007-0.079) nmol/L, median percentage difference 24.9% (7.8-83.3%). When the two sampling conditions were compared, plasma-free 3-methoxytyramine (3-MT), norepinephrine and dopamine concentrations did not differ. Conclusions Blood sampling by venipuncture resulted in statistically significant higher concentrations of MN, NMN and epinephrine compared to sampling by means of an indwelling cannula. However, differences were small. For most patients it seems justifiable to collect blood via venipuncture.